Investigating the anti-termite property of African birch extract for treatment of some selected susceptible timbers - Uwemedimo Nyong Wilson; Nasir Yakubu Muhammed; Mohammed Abdulkareem Adisa; Samson Olalekan Odeyemi (Discover Applied Sciences)
Abstract Timber, an organic material found in nature, has long served as a fundamental resource for constructing bridges, buildings, and various other structures. The search for eco-friendly timber preservatives led to this study, which aimed to develop a non-synthetic preservative from A. leiocarpus extract and test its effectiveness on Triplochiton scleroxylon, Alstonia boonei, and Ceiba pentandra. A total of 120 wood samples (30 per specie) were prepared according to ASTM D3345-22 (2022). Moisture content and density were determined per BS EN 408: 2010. Extracts were prepared by soaking 3 kg of A. leiocarpus shavings in 30 L of water for 21 days, followed by phytochemical analysis. The cold-soak treatment method was applied, and samples were subjected to a graveyard test following ASTM D1758. Stakes were buried in termite-infested soil and retrieved after 6 weeks for gravimetric weight loss analysis. Phytochemical analysis detected alkaloids, saponins, phenols, tannins, terpenoids, cardiac glycosides, and anthraquinones, while flavonoids, steroids, and phlobatannins were absent. Concentration of Tannin was found to be 13.34 mg/100 g, Saponins 9.82 mg/100 g, Alkaloid 4.96 mg/100 g, Flavonoid 2.04 mg/100 g, and Anthraquinone 1.84 mg/100 g achieved in a 12-day average decoction period. Ceiba pentandra exhibited the highest deterioration at 89.71%, followed by Alstonia boonei at 42.88% and Triplochiton scleroxylon at 39.80%. The graveyard test showed that preservative-treated wood samples suffered less termite damage than untreated samples, but the test does not fully capture timber durability. Statistical analysis indicates that A. leiocarpus extract possesses termiticidal potential. Further studies on its long-term efficacy, application methods, and environmental impact are recommended.